2013
DOI: 10.1186/1471-2164-14-353
|View full text |Cite
|
Sign up to set email alerts
|

Transcription analysis of the porcine alveolar macrophage response to porcine circovirus type 2

Abstract: BackgroundPorcine circovirus type 2 (PCV2) is the causal agent of postweaning multisystemic wasting syndrome (PMWS), which has severely impacted the swine industry worldwide. PCV2 triggers a weak and atypical innate immune response, but the key genes and mechanisms by which the virus interferes with host innate immunity have not yet been elucidated. In this study, genes that control the response of primary porcine alveolar macrophages (PAMs), the main target of PCV2, were profiled in vitro.ResultsPAMs were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 74 publications
5
30
2
Order By: Relevance
“…Previous studies have reported that PCV2 infection induces porcine IL-8 expression both in vivo and in vitro (Chae & Choi, 2011;Darwich et al, 2003;Li et al, 2013;Mavrommatis et al, 2014). To confirm these findings, IL-8 secretion from PCV2-infected PAMs was measured at the protein level by ELISA.…”
Section: Pcv2 Infection Triggers Il-8 Secretion In Pamsmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies have reported that PCV2 infection induces porcine IL-8 expression both in vivo and in vitro (Chae & Choi, 2011;Darwich et al, 2003;Li et al, 2013;Mavrommatis et al, 2014). To confirm these findings, IL-8 secretion from PCV2-infected PAMs was measured at the protein level by ELISA.…”
Section: Pcv2 Infection Triggers Il-8 Secretion In Pamsmentioning
confidence: 82%
“…Interstitial pneumonia is frequently observed in pigs suffering from naturally acquired PMWS or experimental PCV2 infection (Chae & Choi, 2011;Darwich et al, 2003a). It has been reported that PCV2 infection triggers IL-8, IL-1b and TNF-a expression in porcine alveolar macrophages (PAMs), monocyte-derived dendritic cells, and PBMCs (Darwich et al, 2003b;Li et al, 2013;Mavrommatis et al, 2014). Moreover, upregulated mRNA expression of IL-1a and IL-8 was found in an in vivo model of PCV2-associated respiratory disease (Chae & Choi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During PCV2 infection, the expression levels of cellular genes are extensively modulated, and the resulting differentially expressed proteins are involved in the cytoskeleton, stress response, macromolecular biosynthesis, energy metabolism, ubiquitin-proteasome pathway, signal transduction, gene regulation, and immune response [38][39][40][41][42][43][44][45]. The virus-host interactions related to PCV2 proliferation are shown in Fig.…”
Section: Interactions Related To Pcv2 Propagationmentioning
confidence: 98%
“…Additionally, infection with this virus increases cellular autophagy to enhance PCV2 proliferation in cells. The arrows indicate activation, whereas T lines indicate inhibition Virus Genes and TLR9 pathways [40]. Interleukin (IL)-2 can induce cell proliferation and PCV2 replication in peripheral blood lymphocytes [99].…”
Section: Pcv2-induced Cell Autophagymentioning
confidence: 99%
See 1 more Smart Citation